Θεόπνευστος and its implications for the concept of scripture in 2 Timothy 3:14-17 - Adebayo, Oluwarotimi Paul (Stellenbosch : Stellenbosch University, 2019)
Thesis (MTh)--Stellenbosch University, 2019